A relação entre o saber fazer e o saber sobre o fazer no discurso pedagógico oficial da educação física escolar - Liba, Flávia Roberta Torezin (2012)
This research has the theme the school knowledge of Physics Education, more specifically, the relation theory and practice linked in the pedagogical discourse of the mentioned discipline. The study was conducted according to a mixed research approach that associates quantitative and qualitative aspects, and in an empirical form. It intends to offer subsidies support for the discussion and a better understanding about the process of formation of school knowledge of Physics Education. The research used two documents as the source: the National Curricular Parameters and the Curriculum Proposal of São Paulo State.The search procedures adopted were the documentary analysis, using as theoretical-methodological reference, Bersntein's theory, specifically on those aspects that relate the process of pedagogical discourse of re-contextualization and the concept of classification. The results obtained demonstrate the possibility of finding the process of re-contextualization through analysis of instances that constitute it, besides revealing that the establishment of the relation between the "know-how" and the "know about" in physical education has been more valued in the official pedagogic discourse